APPLICATION OF COLONIAL ARCHITECTURAL DESIGN TO "BANDOENG TEMPO DOELOE" IN KOTA BARU PARAHYANGAN - Hashartyadi, Himawan; Handayani, Sri (Journal of Development and Integrated Engineering, 2023)
Architects have an important role in determining the developmentof architecture. Colonial era architectural style is an architecturaldesign concept that was applied during the Dutch colonial period.Inside there are various architectural styles that are quite differentfrom time to time. This architectural style is divided into 3, namelyIndische Empire, Transitional Colonial Architecture, and ModernColonial Architecture. The development of colonial architecture inIndonesia can be seen from the existence of buildings that adoptEuropean architectural styles in various big cities on the island ofJava, such as Jakarta, Bandung, Jogja, Semarang, and Surabaya.Traces of Colonial Architecture in Bandung can be seen frombuildings in conservation areas such as the Braga area, Dago, andalso in the Diponegoro Street area or the Gasibu area of Bandung.Kota Baru Parahyangan is one of the largest independent cities inthe Greater Bandung area which has a development concept orhistorical pillar, namely having a house building design withcolonial architectural style in the "Bandoeng Tempo Doeloe"corridor area. Based on this development concept, the author aimsto discuss articles on the concept of colonial architecture in the"Bandoeng Tempo Doeloe" area. In addition, the author also hopesthat the discussion of this article can provide a lesson for thegeneral public about colonial architecture, especially in theBandung area. The results of the discussion of this article concludethat the buildings in the "Bandoeng Tempo Doeloe" area adapt tothe three colonial architectural styles, most of which refer tomodern colonial architecture.